1985
DOI: 10.1139/v85-042
|View full text |Cite
|
Sign up to set email alerts
|

Detailed copolymer characterization using ultraviolet spectroscopy

Abstract: (1985).A method is demonstrated for the interpretation of the ultraviolet spectra of styrene-containing copolymers. This method is based on the use of model molecules to approximate the absorption behaviour of the known chromophores and on the statistical estimation of the average spectra of the unknown chromophores. ' The analysis yields directly the copolymer composition and an estimate of the background spectra which arise from the different arrangements of the styril units along the polymer chains. It is s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

1988
1988
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 11 publications
1
6
0
Order By: Relevance
“…This phenomenon is a scattering-related effect of large particles that can be accounted for by using the scattering theory and is classified under a novel category of observed hypochromism designated as macroscopic hypochromism (see Theory section for formal definition). Our experimental evidence as well as previous work done on macromolecules (polystyrene, proteins) [ 9 , 12 ] support the notion that instances of perceived molecular hypochromism reported in encapsulated particle systems can be explained in terms of light scattering and instrumental configuration.…”
Section: Introductionsupporting
confidence: 89%
See 1 more Smart Citation
“…This phenomenon is a scattering-related effect of large particles that can be accounted for by using the scattering theory and is classified under a novel category of observed hypochromism designated as macroscopic hypochromism (see Theory section for formal definition). Our experimental evidence as well as previous work done on macromolecules (polystyrene, proteins) [ 9 , 12 ] support the notion that instances of perceived molecular hypochromism reported in encapsulated particle systems can be explained in terms of light scattering and instrumental configuration.…”
Section: Introductionsupporting
confidence: 89%
“…Such properties make suspended particle systems more complex to model in terms of their physical attributes and make interpretation of the spectrum equally problematic. The light scattering theory of electromagnetic radiation has been shown to provide an effective approach to examining the particle suspensions including polymers [ 9 ], molecular aggregates [ 10 12 ], and microorganisms [ 13 – 15 ]. Successful use of the theory to model multiwavelength spectra of particles requires the knowledge of several important parameters including the chemical composition, particle number, particle size, and particle size distribution (PSD), all of which can be acquired experimentally.…”
Section: Introductionmentioning
confidence: 99%
“…Figure shows the theoretical spectra of polystyrene particles with sizes of 700 nm, 1.4 μm, and 2 μm. These curves were calculated using algorithms developed by García‐Rubio and coworkers .…”
Section: Referring the Results Of The Software Implementation And Thementioning
confidence: 99%
“…Recent spectroscopy studies (Refs. [20][21][22][23][24][25] have demonstrated that it is possible to identify and quantify phenyl and benzoate end groups using uv-vis spectroscopy. The simplicity of these measurements enables the mapping of a broad set of experimental conditions over fhe conzpkte comwsion fmjecfories and opens the possibility of monitoring the number of initiator end groups as a function of the molecular weight in size exclusion chromatography (SEC) experiments Studies of the rate of polymerization to complete conversions coupled with the uv-vis spectroscopy analysis of initiator end groups are beginning to yield quantitative information to investigate the behavior of the rate parameters as a function of conversion, and are providing fundamental data for the testing of hypothesis concerning the kinetics of initiator decomposition and termination mechanisms (Refs.…”
Section: Summary Of Literature Resultsmentioning
confidence: 99%